The Influence of Founding Team Company Affiliations on Firm Behavior - Beckman, Christine M. (Academy of Management Journal, 2006)
This paper's argument is that founding team composition—in particular, members' prior company affiliations—shapes new firm behaviors. Firms with founding teams whose members have worked at the same company engage in exploitation because they have shared understandings and can act quickly. Conversely, founding teams whose members have worked at many different companies have unique ideas and contacts that encourage exploration. In addition, firms whose founding teams have both common and diverse prior company affiliations have advantages that allow them to grow. The results suggest team composition is an important antecedent of exploitative and explorative behavior and firm ambidexterity.